IMPLEMENTASI PEMBELAJARAN DEMOKRATIS: Sebuah Studi Tentang Pembelajaran Ski Pada Madrasah Tsanawiyah Di Aceh - Murdani Murdani (Universitas Islam Negeri Ar-Raniry, 2015)
Democratic instruction is a teaching strategy which optimizes the students' roles during the teaching-learning process. The strategy also provides a mutually balanced relationship between the teacher and the students in the classroom. This study aims to class in Islamic junior high schools (MTs) in Aceh Province and to describe the definition, implementation, and any adverse effects on the students when the democratic teaching has not been applied, and the implications toward the students and teachers in the islamic culture and history (SKI). The study found that in general, most teachers of the cultural history of Islam of the MTs in Aceh have implemented the democratic teaching strategy in their classes through discussions, question and answer, and group work. However, some teachers have not yet implemented the strategy due to various factors, such as lack of awareness and unprofessionalism. The positive implications were found in most schools where the teachers implemented the strategy in their classes in the MTs in Aceh. However, schools still need to improve to avoid and solve the adverse implications, such as by improving the quality and quantity of the instructional elements like the teachers, learning facilities, learning evaluation system, curriculum, and relationship with the school surroundings; the students' parents, society, local government, and the related parties of the school.